Rational modification, synthesis and biological evaluation of N-substituted phthalazinone derivatives designed to target interleukine-15 protein. (1st June 2021) - Smadja, Jimmy; Quéméner, Agnès; Maillasson, Mike; Sicard, Benoit; Leray, Aurélien; Arzel, Laurence; Lebreton, Jacques; Mortier, Erwan; Dubreuil, Didier; Mathé-Allainmat, Monique
Graphical abstract: Abstract: Interleukin (IL)-15 is a pleiotropic cytokine structurally close to IL-2 and sharing with the IL-2Rβ and γc receptor (R) subunits. IL-15 plays important roles in innate and adaptative immunity, supporting the activation and proliferation of NK, NK-T, and CD8 + T cells. Over-expression of IL-15 has been shown to participate to the development of inflammatory and autoimmune diseases and diverse T cell malignancies. This study is in continuity of our previous work through which a family of small-molecule inhibitors impeding IL-15/IL-2Rβ interaction with sub-micromolar activity has been identified using pharmacophore-based virtual screening and hit optimization methods. With the aim to improve the efficacy and selectivity of our lead inhibitor, specific modifications have been introduced on the basis of optimized SAR and modelisation. The new series of compounds generated have been evaluated for their capacity to inhibit the proliferation as well as the down-stream signaling of IL-15-dependent cells and to bind to IL-15.